Akibat Hukum Terhadap Anak Hasil Perkawinan Siri Perspektif UU Nomor 1 Tahun 1974 Tentang Perkawinan Di Desa Rantau Mapesai Kecamatan Rengat Kabupaten Indragiri Hulu Tahun 2019 - IMELDALIUS SH MH (STIA Indragiri, 2019)
In the UUP, it is clear that a marriage that is legally recognized by the State is a marriage that is legal in the respective religion and legally by the State of Indonesia. However, in reality there are still many people who carry out siri marriages, even though the reasons for carrying out unregistered marriages vary and also cause problems before and after the divorce, where the rights of the wife do not get legal certainty and also the rights of the child towards the father, because the child resulting from a siri hanay marriage has a civil relationship with his mother and his mother's family, and besides that, he will also have difficulties in managing family cards, birth certificates and other